Synthesis, physical and chemical properties of 5-(adamantane-1-yl)-4-amino-1,2,4-triazole-3-thiol derivatives - Odyntsova, V. M.; Одинцова, Віра Миколаївна (ЗДМУ, 2016)
Implementation of new highly effi cient drugs in medical practice is one of the most urgent problems of modern pharmaceutical industry. Scientifi c achievements of heterocyclic compounds’ chemistry clearly show that 1,2,4-triazole system is promising object of such research. It should be also noted that compounds, with adamantane “core” deserve special attention. The aim of our work was to synthesize new derivatives of 5-(adamantan-1-yl)-4-amino-1,2,4-triazole-3-thiols, and to investigate their physical and chemical properties. Materials and methods. Chemical names of compounds are given in accordance with IUPAC nomenclature (1979) and the IUPAC recommendations (1993). Study of physical-chemical properties of obtained compounds was carried out in accordance with methods listed in the State Pharmacopia of Ukraine. Melting point was determined on the automatic device for determining the melting temperature Stanford Research Systems OptiMelt MPA100 (manufacturing USA). Elemental composition of new compounds was established on the elemental analyzer Elementar Vario EL cube (CHNS) (standard – sulfanilamide). The data of elemental analysis correspond to the calculated one. 1H NMR spectra of compounds were recorded using spectrometer “Mercury 400”. Chromato-mass spectra were recorded on a spectrometer Agilent 6890N/5973N/FID production of Agilent Technologies. Results. The concept of creating biologically active molecules is fi rst of all directed on combining fragments of different molecules in one. Theoretically, this could lead to the new types of compounds with pharmacological action, and sometimes to the potentiation of existing biological properties. Further actions are focused on the physical and chemical properties study of these compounds. To establish the structure of 5-(adamantan-1-yl)-4-((aryl-, heteryl)ilyden)-amino-1,2,4-triazole-3-thiols we used an integrated approach with the use of modern physical and chemical methods of analysis. Individuality of compounds in each case is confi rmed by chromatography. The results of the chromatographic investigations showed that in all cases the constants of pseudo molecular ions peaks of obtained 5-(adamantan-1-yl)-4-((aryl-, heteryl)yliden) amino-1,2,4-triazole-3-thiols coincide with theoretical calculations of molecular masses. Conclusions. New 5-(adamantan-1-yl)-4-((aryl-, heteryl)yliden)amino-1,2,4-triazole-3-thiols have been synthesized, their structure and individuality has been confi rmed by complex of modern physical-chemical methods of analysis. In all cases, the values of the investigated physical-chemical constants coincide with the calculated ones. В умовах сучасного розвитку світової фармацевтичної галузі найактуальнішою проблемою залишається впровадження у практику нових високоефективних ліків. Наукові досягнення хімії гетероциклічних сполук переконливо доводять перспективність використання 1,2,4-тріазолу. Окремої уваги заслуговують сполуки, в молекулах яких типовим фармакофором виступає «ядро» адамантану. Мета роботи – синтезувати нові похідні 5-(адамантан-1-іл)-4-аміно-1,2,4-тріазол-3-тіолів, дослідити їхні фізико-хімічні властивості. Матеріали та методи. Хімічні назви сполук наведені згідно з номенклатурою IUPAC (1979) і рекомендаціями IUPAC (1993). Дослідження фізико-хімічних властивостей сполук, що отримали, здійснили відповідно до методів, які наведені в Державній Фармакопеї України. Температуру плавлення визначили на автоматичному приладі для визначення температури плавлення Opti Melt Stanford Research Systems MPA100 (США). Елементний склад нових сполук встановлено на елементному аналізаторі Elementar Vario EL cube (CHNS) (стандарт – сульфаніламід). 1H ЯМР-спектри сполук записані за допомогою спектрометра «Mercury 400». Хромато-мас-спектри реєстрували на спектрометрі Agilent 6890N/5973N/FID (Agilent Technologies). Результати. Концепція створення біологічно активних сполук, перш за все – це направлене моделювання внаслідок поєднання фрагментів різних молекул в одній, що може призвести до появи сполук із новими видами фармакологічної дії, а іноді до потенціювання наявних біологічних властивостей. Подальші дії орієнтовані на дослідження фізико-хімічних властивостей сполук. Для встановлення будови 5-(адамантан-1-іл)-4-((арил-, гетерил)іліден)аміно-1,2,4-тріазол-3-тіолів використовували комплексний підхід із використанням сучасних фізико-хімічних методів аналізу. Індивідуальність сполук у кожному випадку підтверджена хроматографічно. За результатами хроматографічних досліджень встановили, що в усіх випадках константи піків псевдомолекулярних іонів отриманих 5-(адамантан-1-іл)-4-((арил-, гетерил)іліден)аміно-1,2,4-тріазол-3-тіолів збігаються з теоретичними розрахунками молекулярних мас молекул. Висновки. Уперше синтезований ряд нових 5-(адамантан-1-іл)-4-((арил-, гетерил)іліден)аміно-1,2,4-тріазол-3-тіолів, будова та індивідуальність яких підтверджена комплексним використанням сучасних фізико-хімічних методів аналізу. У всіх випадках значення досліджених фізико-хімічних констант збігаються із розрахунковими теоретичними показниками.
Синтез, фізико-хімічні властивості похідних 5-(адамантан-1-іл)-4-аміно-1,2,4-тріазол-3-тіолів
Keywords: 1,2,4-triazole; chemical synthesis; chemical properties; 1,2,4-тріазол; синтез; хімічні властивості